2015
DOI: 10.1093/jxb/erv077
|View full text |Cite
|
Sign up to set email alerts
|

Root length densities of UK wheat and oilseed rape crops with implications for water capture and yield

Abstract: Root length density (RLD) was measured to 1 m depth for 17 commercial crops of winter wheat (Triticum aestivum) and 40 crops of winter oilseed rape [Brassica napus; oilseed rape (OSR)] grown in the UK between 2004 and 2013. Taking the critical RLD (cRLD) for water capture as 1cm cm(-3), RLDs appeared inadequate for full water capture on average below a depth of 0.32 m for winter wheat and below 0.45 m for OSR. These depths compare unfavourably (for wheat) with average depths of 'full capture' of 0.86 m and 0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 59 publications
6
51
2
1
Order By: Relevance
“…Furthermore, the maximal root length densities were considerably higher in the silty soil than in the stony soil (note the difference in color scale). The root density distributions showing maximal densities at greater depths are markedly different from the root density profiles that have been observed for winter wheat using soil coring in loamy soil (Zhang et al, 2004) and in soils with seven different textures (from clay to sandy loam) (e.g., White et al, 2015;Zhang et al, 2004). This might on the one hand be due to a great amount of water stored at those depths in the silty soil but probably also due to nutrient distribution in the soil profile at this site, which might have promoted root development in deeper soil layers (Thorup-Kristensen et al, 2009;Yang et al, 2003).…”
Section: Effect Of Water Treatment On Crop and Root Developmentcontrasting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, the maximal root length densities were considerably higher in the silty soil than in the stony soil (note the difference in color scale). The root density distributions showing maximal densities at greater depths are markedly different from the root density profiles that have been observed for winter wheat using soil coring in loamy soil (Zhang et al, 2004) and in soils with seven different textures (from clay to sandy loam) (e.g., White et al, 2015;Zhang et al, 2004). This might on the one hand be due to a great amount of water stored at those depths in the silty soil but probably also due to nutrient distribution in the soil profile at this site, which might have promoted root development in deeper soil layers (Thorup-Kristensen et al, 2009;Yang et al, 2003).…”
Section: Effect Of Water Treatment On Crop and Root Developmentcontrasting
confidence: 82%
“…On the other hand, some studies indicated that root length densities estimated from rhizotubes may underestimate the root densities in surface soil layers due to temperature effects (Fitter et al, 1998) or roots growing parallel to the horizontal plane not intersecting the tube surface (Meyer and Barrs, 1991). We obtained root lengths ranging from 1.5 to 7.0 km m −2 , which is within the range of the results from White et al (2015) who investigated root development of 11 winter wheat varieties in 4 different soils (from clay to sandy loam) in the UK. They found an average of 9.8 km m −2 from the samples to 1 m depth.…”
Section: Effect Of Water Treatment On Crop and Root Developmentsupporting
confidence: 81%
“…S2). The shape of the drying curves reflects the general distribution of root biomass in a soil profile, with most root activity occurring in the upper 50 cm (White et al 2015). Most differences in absolute terms were small, indicating that the EMI method was able to discern relatively subtle genotypic differences in soil moisture extraction.…”
Section: Differences Between Wheat Linesmentioning
confidence: 99%
“…This applies to both root system architecture and function. The 'core-break' method for wheat Wasson et al 2014;White et al 2015) or the "shovelomics" approach for maize (Trachsel et al 2011) provide methods for phenotyping root density or architecture in the field, but excavations remain labour intensive and time-consuming. An alternative to excavating the root systems is to measure soil water content as a function of depth and infer root activity from those measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation